The M2DM Project - Larizza, C.; Bellazzi, R.; Stefanelli, M.; Ferrari, P.; De Cata, P.; Gazzaruso, C.; Fratino, P.; D’Annunzio, G.; Hernando, E.; Gomez, E.J. (Methods of Information in Medicine, 2006)
Objectives: This paper presents a multi-access service for the management of diabetes mellitus patients and the results of its assessment in two Italian clinical sites.Methods: The service was evaluated for one year in order to prove the advantages of these kind of systems from different points of view. In this paper the clinical, usability and technical outcomes are presented.Results: The evaluation results show that, thanks to the high flexibility of the implemented service, the tele-medicine management of diabetes patients is feasible, well accepted by patients and clinically effective. However, in Italy the problem of quantifying the reimbursement rate of telematic services and the impact they have on the organization are factors that may hamper their introduction in routine clinical practice.Conclusions: The evaluation study showed that the telemedicine intervention has been satisfactory both for physicians because it allows to constantly monitor the patients’ blood glucose level and for patients because it strengthens their motivation to self-monitor the metabolic situation.
Keywords: Telemedicine; diabetes mellitus; blood glucose self-monitoring